Chemotherapy-induced peripheral neurotoxicity - Cavaletti, Guido (Henry Stewart Talks, 2020)
Clinical features of CIPN induced by different chemotherapy drugs, Potential CIPN biomarkers, Assessment of CIPN, Chemotherapy drugs and their properties, New drugs and current research